Classifying early-onset colorectal cancer according to tumor location: new potential subcategories to explore - Perea, José (Am J Cancer Res, 2015)
Early-onset Colorectal Cancer (ECRC) represents a significant and increasing proportion of Colorectal Cancer (CRC), but it is a heterogeneous entity that probably encompasses specific subclasses. On the premise that the carcinogenetic mechanism and progression of CRC may differ with location, we analyzed molecular and clinical characteristics of ECRC according to tumor location in order to identify more homogeneous subgroups of CRC. Right-sided ECRC is a subset in which most Lynch Syndrome cases are found, with earlier stages at diagnosis and better prognosis. At this location the CpG Island Methylator Phenotype (CIMP) is predominant and Chromosomal Instability (CI) is rare. Left-sided ECRC appears as a transitional or intermediate location, except for CI tumors, that seem to predominate at this location. Finally, rectal ECRC shows Microsatellite Stability, CIMP low-0 and low CI - with recurrent altered chromosomal regions in common with left-sided ECRC-, possibly in relation with Microsatellite And Chromosomal Stable tumors, but with an unexpected familial component and worse prognosis. All this suggest that the molecular basis of ECRC varies with tumor location, which could affect the clinical management of patients.